Table of Content - -, (Journal of Economic, Administrative and Legal Sciences, 2025)
:Table of Content• The Impact of Blockchain Technology Adoption on Audit Planning: An Exploratory Study on Saudi Audit Firms (2022-2023)Mr. Abdulaziz Ali Alzahrani ,Dr. Yousef Ali Alwardat, Dr. Mohammad Aboalkar Wazzan• The Impact of Strategic Leadership on Enhancing Organizational Reputation: A Field Study on Administrative Employees at King Abdulaziz University in Jeddah GovernorateMr. Saleh Jamaan Saleh Al-Zahrani• Impact of Modern Digitization of Logistics Operations on Supply Chain Performance: A Case Study of Almarai Company, Saudi ArabiaAsst-Prof. Hanan Rashid Albalwy• The role of governance in raising the level of financial disclosure and its impact on the quality  and integrity of financial reports (Field study 2023-2024)Lawyer \ Hind Mansour Al-Balawi• The impact of the management by values (MBV) on the competitiveness of Saudi Arabia Hospitals Al-Qassim Region Dr. Gamaleldeen Osman Althair, Dr. Mohieldin Ali Mohieldin• The Impact of Forensic Accounting and Corporate Governance on Enhancing Accounting TransparencyLecturer \ Hanan Salih Jabur• The Knowledge Economy and Human Capital " A Literature Review"Ms. Halima Sharif Muhammad Al-Amrani, Prof. Reem Ali Al-Rabghi,  Co-Prof. Rabab Abdulrahman Mujallid• The Role of 5S Workplace Organization in Promoting A Safe Work Environment in the Petroleum Sector “An Exploratory Study of the Opinions of Oil Sector Officials in Najaf Al-Ashraf”Dr. Yaser Hameed Mohammad Al-Hashimee, Prof. Mahdi Mohammadi Nasab• International Legal and Instiutional Mechanisms for Combating CorruptionLawyer \ Animar Ali Zaher
Keywords: The Journal of Economic, Administrative and Legal Sciences